Eye to Eye Sports Journalist Christine Brennan - Rubini, Julie (Book collections on Project MUSE., 2019)
"Christine Brennan, the USA Today sports columnist, author, and commentator, uses her voice to advocate for diversity and equality in the world of sports, and her wisdom to encourage future journalists. Her passion for sports was sparked by her dad, who encouraged her to participate in athletics and, as he said, 'smell the game'--go watch baseball and football games together. As a child, Christine wrote daily entries in her diary and listened to play-by-play coverage on her radio. She pursued this love of words through journalism school and applied her passion for sports by reporting on them for various newspapers. Since then, she has portrayed the setbacks and triumphs of athletes, all the while fighting her own battles for success--and respect--as a female journalist. From knocking down barriers in NFL locker rooms to covering every Olympics since 1984 to being the go-to commentator whenever scandal occurs in the sports world, Christine Brennan has done it all. Eye to Eye invites young readers to learn more about this remarkable journalist and perhaps to nurture their own dreams of investigating and telling important stories"--